Transformational Leadership Dynamics and Its Influence on Innovation in the Realm of Entrepreneurial Management - Susantinah, Nugrahini; Jusman, Ikhsan Amar; M. Ardi (ADMAN: Journal of Contemporary Administration and Management, 2023)
In the era of globalization and intensifying business competition, an organization's ability to innovate has become crucial for its sustainability and business continuity. Entrepreneurial management has emerged as a vital approach in navigating rapidly changing market dynamics. This research aims to analyze the relationship between the dynamics of transformational leadership and the level of innovation in the context of entrepreneurial management. The study employed an in-depth literature examination using qualitative analysis, intending to gain a comprehensive understanding of the subject matter spanning the years 1990 to 2023. The results of the study indicate that the dynamics of transformational leadership have proven to be a driving force for innovation in the domain of entrepreneurial management. Transformational leadership, through its ability to provide inspiration, motivation, and guidance to teams, creates an environment that fosters creativity and experimentation. This is not only related to achieving current goals but also to shaping the future of the organization through the development of new and talented leadership.